PEMBELAJARAN ISU SOSIOSAINTIFIK UNTUK MENINGKATKAN KETERAMPILAN PENGAMBILAN KEPUTUSAN: SYSTEMATIC LITERATURE REVIEW - Rahmadani, Amalia; Yusal, Yulianti; Kisworo, Banu (Universitas Tanjungpura, 2026)
This study aims to systematically examine the effect of socio-scientific issues-based learning on improving students’ decision-making skills in science learning. The research method used was a systematic literature review employing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. Article searching was conducted through the Google Scholar database with the inclusion criteria of articles published between 2020 and 2025, discussing socio-scientific issues and decision-making skills in the context of science education, and published in national journals. A total of 80 articles were identified at the initial stage, of which three articles met the inclusion and quality criteria and were analyzed further. The results of the analysis indicate that socio-scientific issues-based learning has the potential to enhance students’ decision-making skills, particularly through the use of SSI-based electronic modules and the implementation of innovative learning models such as RICOSRE and ReClif. SSI-based learning equips students to identify problems, collect and evaluate information, consider alternative solutions, and determine the most appropriate decision. This review shows that socio-scientific issues-based learning is a contextual approach to strengthening students’ decision-making skills in science learning, and that further development is needed focusing on the design and evaluation of decision-making skills.